Acupuncture promotes muscle cells ATP metabolism in ST36 acupoint local exerting effect by activating TRPV1/CaMKII/AMPK/PGC1α signaling pathway - Zhihan Chen; Kaifang Yao; Xinrui Wang; Yangyang Liu; Simin Du; Shenjun Wang; Yuxin Fang; Yuan Xu; Zhifang Xu; Xiaowei Lin; Yi Guo (Chinese Medicine)
Abstract At present, a number of studies have shown that acupuncture at Zusanli (ST 36) can relieve pain, but the changes of local microenvironment in the acupoint area after acupuncture have not been elucidated. As a temperature and pain receptor, TRPV1 plays an important role in pain perception and inflammation regulation. In this study, RT-PCR technique was used to screen the types of mechanically sensitive ion channels in the local response to acupuncture in the acupoint area, and western bolt technique was used to verify in gene knockout and antagonist injection mice. Immunofluorescence double labeling technique was used to further determine the key cell types of TRPV1-mediated acupuncture analgesia. Finally, through the combined analysis of proteomics and phosphorylated proteomics, the local signaling pathways of acupoints that can be activated by acupuncture were analyzed. This study systematically explored the analgesic effect of acupuncture on inflammatory pain in mice and its mechanism. The study found that acupuncture can significantly improve the thermal pain threshold and mechanical pain threshold in mice, showing a significant analgesic effect. Further analysis revealed that this analgesic effect was closely related to the up-regulation of local TRPV1 expression at ST36, and its deletion or functional inhibition would significantly weaken the analgesic effect of acupuncture. In addition, we also found that acupuncture in the deep muscle layer can more effectively promote the expression and activity of TRPV1 than in the superficial fascia layer, and muscle cells are the key cell types of TRPV1-mediated acupuncture analgesia. Finally, through the combined analysis of multi-omics, it was clear that acupuncture could activate the local signal pathway TRPV1/CaMKII/AMPK/PGC1α to exert analgesic effect. In conclusion, this study not only confirmed the analgesic effect of acupuncture on inflammatory pain in mice, but also revealed the core role of TRPV1 in the mechanism of acupuncture analgesia, especially the important contribution of TRPV1 expression and activity in the muscle layer of ST36 acupoint to the analgesic effect of acupuncture, which provided a new scientific basis and potential therapeutic target for acupuncture treatment of inflammatory pain. Graphical abstract